SNOW STABILIZATION FOR ROADS AND RUNWAYS - Wuori,Albert F. (1963)
A stdy of methods of stabilizing snow for roads and runways was conducted on the Greenland Ice Cap during the summer of 1959. Ten test lanes were constructed to determine the effect of various machine speeds, cutting, and compaction techniques; 7 lanes were dry-processes, 3 lanes dry- and heat-processed. The dry-processing methods included use of Snowblast and Peter miller rotary plows followed by leveling and compaction with a D-8 low ground pressure tractor. A T-5 Snow Packer was used in the heat-processing tests. Tests showed that dry processing produced a pavement structure capable of supporting certain types of wheeled cargo aircraft after 3 weeks of age hardening. Apparently heat processing of a thin surface layer is required to support aircraft with tire pressures exceeding 100 psi. (Author)